The firefly effect : - Douglas, Kimberly (Wiley, 2009)
The Firefly Effect, Kimberly Douglas presents inspiring yet pragmatic insights into getting your entire team firing on all cylinders and aiming in the right direction. Comparing the difficult act of harnessing and capturing creativity to the act of catching fireflies on a summer night.